Концептуалізація розвитку особистого бренду в цифровому просторі - Сергієнко, Олена Андріанівна; Швець, Анастасія Дмитрівна; Калашник, Марія Юріївна (My University, 2025)
У статті здійснено концептуалізацію розвитку особистого бренду як цілісного стратегічного процесу у цифровому середовищі. Розкрито сутність особистого бренду як інструменту професійного позиціонування, побудови довіри та підвищення конкурентоспроможності. На основі аналізу актуальних підходів до брендингу в умовах цифровізації запропоновано концепцію розвитку особистого бренду, що охоплює ключові етапи: визначення унікальної ціннісної пропозиції, формування візуального образу, створення контент-стратегії, вибір цифрових платформ для просування, а також побудову сталих комунікацій з аудиторією. Особливу увагу приділено ролі соціальних мереж у просуванні бренду, важливості автентичності та репутаційної стабільності. Окреслено основні виклики цифрового середовища – зокрема ризики репутаційних втрат, негативного інформаційного фону, кризових ситуацій – та запропоновано практичні підходи до їх нейтралізації: моніторинг онлайн-згадок, управління зворотним зв’язком, стратегічне вибудовування довіри. Представлена концепція може бути корисною для фахівців у сфері маркетингу, PR, підприємництва та особистого розвитку.

The article presents a conceptualisation of personal brand development as a comprehensive and strategic process in the digital environment. A personal brand is seen as a key tool for self-presentation, audience engagement and longterm professional growth. The proposed conceptual approach outlines the core components of brand development: defining unique value propositions, designing a visual identity, building a content strategy, selecting effective digital platforms, and maintaining authentic interaction with audiences. Special attention is given to the role of social media in shaping brand visibility and the need to tailor content to audience expectations. The study highlights that today's consumers are increasingly sensitive to authenticity, emotional connection and personalised communication, which have a significant impact on brand perception and loyalty. As a result, personal branding should not be seen as a one-off activity, but as an ongoing, adaptive process that responds to changes in audience behaviour and media formats. Key challenges and risks are identified, such as reputational threats, negative feedback and the volatility of digital attention. Reputation management strategies are proposed, including monitoring online mentions, responding quickly to feedback and building long-term trust through transparent communication. The paper emphasises the importance of strategic planning and content consistency as fundamental principles of sustainable personal brand development. The conceptual model proposed in the study integrates both strategic branding practices and adaptive communication techniques relevant in today's highly competitive and dynamic digital landscape. The practical value of the findings lies in their applicability for marketing professionals, entrepreneurs, digital content creators, PR specialists and opinion leaders who wish to build a distinctive and resilient personal brand in the informationsaturated online environment.
Conceptualisation of personal brand development in the digital space
Keywords: бренд; особистий бренд; концепція; соціальні мережі; бізнес; стратегія; репутація; конкурентоспроможність; цифровий простір; brand; personal brand; concept; social networks; business; strategy; reputation; competitiveness; digital space